2004
DOI: 10.1176/appi.ajp.161.7.1204
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Alcoholism in 243 Mission Indians

Abstract: Understanding the course of Mission Indian alcoholism can help identify unique alcohol-related phenotypes as well as guide the development of treatment and prevention programs in this underserved population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
147
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 91 publications
(169 citation statements)
references
References 45 publications
15
147
2
Order By: Relevance
“…However, both advancing age and younger age at onset of alcohol dependence were associated with increased duration of alcohol dependence. These data are consistent with previous findings in this sample that alcohol dependence runs a typical clinical course which includes duration as well as symptomatology (3). These data are not consistent with the notion that, from the standpoint of remission, there may be two groups of alcohol dependent individuals: those with early onset who have a shorter course of alcoholism and those with later onset who have a longer course that has been suggested for other populations (16,40).…”
Section: In Contrast To Dawson and Colleaguessupporting
confidence: 83%
See 1 more Smart Citation
“…However, both advancing age and younger age at onset of alcohol dependence were associated with increased duration of alcohol dependence. These data are consistent with previous findings in this sample that alcohol dependence runs a typical clinical course which includes duration as well as symptomatology (3). These data are not consistent with the notion that, from the standpoint of remission, there may be two groups of alcohol dependent individuals: those with early onset who have a shorter course of alcoholism and those with later onset who have a longer course that has been suggested for other populations (16,40).…”
Section: In Contrast To Dawson and Colleaguessupporting
confidence: 83%
“…The available evidence suggests that rates of remission from alcohol dependence are also substantial in Native American communities (3)(4)(5)23). Ehlers and colleagues (3), in a study of the first 243 American Indian adults who participated in the present study, found a remission rate of 61% from DSM-III-R alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%
“…The demographic characteristics of this sample are similar to available information for the tribe from US Census data. As reported previously in this population [see Ehlers et al, 2004] a total of 280 out of a larger sample of 466 participants (60%) met the criteria for a lifetime DSM-III-R diagnosis of alcohol dependence. Men were significantly more likely to be alcohol dependent (N ¼ 74%) than women (N ¼ 53%) (w 2 ¼ 9.76, df ¼ 1, P < 0.002).…”
Section: Resultssupporting
confidence: 67%
“…They were recruited using a combination of a venue-based method [Kalton and Anderson, 1986;Muhib et al, 2001] and a respondent-driven procedure [Heckathorn, 1997], as previously described [Ehlers et al, 2004].…”
Section: Participantsmentioning
confidence: 99%
“…As part of a larger study examining the etiology of substance use disorders in a community sample of American Indians living on reservations (see Ehlers et al, 2001Ehlers et al, , 2004Ehlers et al, , 2007Gilder et al, 2004Gilder et al, , 2009), the present study applied IRT methods to accomplish two specifi c aims: (a) to evaluate whether cannabis misuse symptoms assess a continuous latent trait that indexes the severity of cannabis use in both Native Americans living on reservations and European Americans and (b) to evaluate whether individual cannabis misuse symptoms differentially index severity in these two populations. Because the Native American community under study has been shown to exhibit very high rates of substance use disorders (e.g., 70% alcohol dependent, 60% cannabis dependent), we chose to use an equally affected population of European Americans for the present report, the University of California, San Francisco (UCSF) Family Alcoholism Study population (70% alcohol dependent, 44% cannabis dependent), which is a nationwide population-based sample selected for the presence of alcohol dependence (Ehlers et al, 2010).…”
mentioning
confidence: 99%